2016
DOI: 10.1021/acs.analchem.6b02408
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Chemically Fixed Cells in Preparation for NanoSIMS

Abstract: In this work, we have employed time-of-flight secondary ion mass spectrometry (ToF-SIMS) to image chemically fixed adrenal cells prepared for transmission electron microscopy (TEM) and subsequent high-spatial-resolution NanoSIMS imaging. The sample fixation methodology preserves cell morphology, allows analysis in the ultrahigh vacuum environment, and reduces topographic artifacts, thus making these samples particularly favorable for ToF-SIMS analysis. ToF-SIMS imaging enables us to determine the chemistry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“… 37 The corrected MDV of intracellular metabolites was mapped onto the central carbon metabolism pathway using VANTED 38 connected to SBGN plugin. 39 NanoSIMS data were analyzed using WinImage software (Cameca) to obtain 13 C 14 N/ 12 C 14 N and 12 C 14 N images and ImageJ 40 with openMIMS plugin 41 software (MIMS, Harvard University, Cambridge, MA; ) to extract the values of each detected ion. Linear regression analysis and Pearson’s correlation coefficient for VOCs, and Michaelis–Menten equation for calculating isotopic steady state were performed using Graphpad Prism 7.0 software (Graphpad Software, Inc., San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“… 37 The corrected MDV of intracellular metabolites was mapped onto the central carbon metabolism pathway using VANTED 38 connected to SBGN plugin. 39 NanoSIMS data were analyzed using WinImage software (Cameca) to obtain 13 C 14 N/ 12 C 14 N and 12 C 14 N images and ImageJ 40 with openMIMS plugin 41 software (MIMS, Harvard University, Cambridge, MA; ) to extract the values of each detected ion. Linear regression analysis and Pearson’s correlation coefficient for VOCs, and Michaelis–Menten equation for calculating isotopic steady state were performed using Graphpad Prism 7.0 software (Graphpad Software, Inc., San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The lysosome was identied as a main accumulation region of OsO 4 . 69 Veith and colleagues combined SIMS with fast micro X-ray uorescence spectroscopy (m-TRF) to detect CeO 2 particles in biological tissue sections. 70 m-TRF allows a fast elemental analysis of big tissues, such as lung tissue.…”
Section: Nanosims and Super-resolution Microscopymentioning
confidence: 99%
“…The IC50 values of the different 13 C-enriched plasmodiones against P. berghei blood stage parasites confirmed that the 13 C-enrichment did not affect the antimalarial activity of the lead drug. The uniformly 13 C-enriched plasmodione will be used to elucidate the drug metabolism studies 41 and the cellular localization of the drug and its metabolites using nanoSIMS imaging 42,43,44 . In addition to the 13 C-labeled compounds, we prepared a series of putative plasmodione metabolites.…”
Section: Discussionmentioning
confidence: 99%